China's Trade in Steel Products: Evolution of Policy Goals and Instruments - Peter Thomas in der Heiden (The Copenhagen Journal of Asian Studies, 2014)
There is a growing consensus in development economics suggesting that successful economic policies feature a combination or succession of inward- and outward-oriented strategies. This article asks whether the Chinese government is pursuing such a mixed approach, which seeks to both harness opportunities from increased trade and investment and, at the same time, promote the development of domestic industries as well as import substitution. Following China's World Trade Organization accession, most export promotion measures became illegal. Policy makers were thus deprived of an effective tool for steering the international business activities of firms through administering incentive and control mechanisms. Their goal of promoting structural change in industries crippled by large overcapacity, low technology levels and low concentration ratios, was thus greatly complicated. Using the steel industry as an example, the article suggests that differentiated export steering continues to exist. It then goes on to ask under what conditions, in what ways and to what extent authorities are acting to harmonize firms' export behaviour with their long-term industrial development conceptions. The article finds that trade policy is not only product sensitive but dependent on technological sophistication, with high-tech products enjoying more favourable treatment.